2021
DOI: 10.1101/2021.01.11.426044
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human colorectal pre-cancer atlas identifies distinct molecular programs underlying two major subclasses of pre-malignant tumors

Abstract: Most colorectal cancers (CRCs) develop from either adenomas (ADs) or sessile serrated lesions (SSLs). The origins and molecular landscapes of these histologically distinct pre-cancerous polyps remain incompletely understood. Here, we present an atlas at single-cell resolution of sporadic conventional tubular/tubulovillous ADs, SSLs, hyperplastic polyps (HPs), microsatellite stable (MSS) and unstable (MSI-H) CRC, and normal colonic mucosa. Using single-cell transcriptomics and multiplex imaging, we studied 69 d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 112 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Single-cell RNA-sequencing (scRNA-seq) and analysis. InDrop scRNA-seq and analysis were performed on 2 independent (discovery and validation) cohorts of human colon samples as previously described 24 . These data are publicly available through the Human Tumor Atlas Network (https://data.humantumoratlas.org/) 50 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Single-cell RNA-sequencing (scRNA-seq) and analysis. InDrop scRNA-seq and analysis were performed on 2 independent (discovery and validation) cohorts of human colon samples as previously described 24 . These data are publicly available through the Human Tumor Atlas Network (https://data.humantumoratlas.org/) 50 .…”
Section: Methodsmentioning
confidence: 99%
“…To understand the topography of MTG16 expression in the human colon, we queried single-cell RNAseq (scRNA-seq) datasets generated from 2 independent cohorts of normal human colon samples 24 . Interestingly, we observed that MTG16 was predominantly expressed in secretory cells (Fig.…”
Section: Mtg16 Is Predominantly Expressed In Secretory Cells In Human and Murine Colonmentioning
confidence: 99%
See 2 more Smart Citations